Hox genes collaborate with helix-loop-helix factor Grainyhead to promote neuroblast apoptosis along the anterior-posterior axis of the Drosophila larval central nervous system. - Sipani, R.; Joshi, R. (Genetics, 2022)
Hox genes code for a family of a homeodomain containing transcription factors that use TALE-HD containing factors Pbx/Exd and Meis/Homothorax to specify the development of the anterior-posterior axis of an organism. However, the absence of TALE-HD containing factors from specific tissues emphasizes the need to identify and validate new Hox cofactors. In Drosophila central nervous system, Hox executes segment-specific apoptosis of neural stem cells (neuroblasts) and neurons. In abdominal segments of larval central nervous system, Hox gene Abdominal-A mediates neuroblast apoptosis with the help of Extradenticle and bHLH factor Grainyhead using a 717-bp apoptotic enhancer. In this study, we show that this enhancer is critical for abdominal neuroblast apoptosis and relies on 2 separable set of DNA-binding motifs responsible for its initiation and maintenance. Our results also show that Abdominal-A and Grainyhead interact through their highly conserved DNA-binding domains, and the DNA-binding specificity of Abdominal-A-homeodomain is important for it to interact with Grainyhead and essential for it to execute neuroblast apoptosis in central nervous system. We also establish that Grainyhead is required for Hox-dependent neuroblast apoptosis in Labial and Sex Combs Reduced expressing regions of the central nervous system, and it can physically interact with all the Hox proteins in vitro. Our biochemical and functional data collectively support the idea that Grainyhead can function as a Hox cofactor and help them carry out their in vivo roles during development.